Evaluating the Effect of Artemisia Aerial Parts Extracts on Candida albicans growth and Shear Bond Strength of Soft Denture Liner - Ayaat Nasser Abdul Nour; Amal Abdul Latif Rashid (Journal of Techniques)
After a period of use in the oral cavity the bond between denture base and soft denture liner weaken or fails creating a suitable environment for fungal colonization. Traditional medical plants that have antifungal agents are considered more safe and with few side effects. The objective of this study was to evaluate the effect of oil and ethanol extracts of Artemisia aerial parts on Candida albicans growth and shear bond strength of soft denture liner. Candida albicans species were isolated and diagnosed, oil and ethanol extracts of Artemisia were prepared, the effect of the extracts on Candida albicans were tested by agar well diffusion test and micro dilution test. Finally, 30 specimens of soft denture liner were prepared for testing shear bond strength by Universal Instron machine before and after incorporation of the extracts. The results showed that all the concentrations of oil extract inhibit the growth of Candida albicans except (12.5 mg/ml) and there were significant differences (P≤0.05) between all concentrations compared with Nystatin except between (100 and Nystatin) mg/ml in which there were no significant difference.  In ethanol extract only the concentrations (100 and 75) mg/ml inhibited the growth of Candida albicans and there were significant differences between all concentrations (P≤0.05) with Nystatin, while shear bond strength was increased in ethanol extract and there were significant differences with the control (P≤0.05), but it was not affected in oil extract and there were no significant differences with the control (P>0.05). Interestingly, it’s concluded that oil and ethanol extracts of Artemisia aerials parts had an effect on Candida albicans, while shear bond strength was not affected by oil extract but increased in ethanol extract.